Design and application of a pharyngeal swab samples collection device (一种咽拭子采集装置的设计及应用) - KANG Jie (康杰); LU Minghui (路明惠); TIAN Ruixi (田润溪); FAN Jiao (范姣); WANG Lin (王琳) (中西医结合护理)
Objective To explore the clinical application effect of a pharyngeal swab samples collection device in nucleic acid testing. Methods A total of 120 hospital staff members who conducted nucleic acid testing were randomly divided into the control group and study group, with 60 cases in each group. The control group adopted regular method of pharyngeal swab samples collection, while the study group used the new type device for pharyngeal swab samples collection. The time cost in sample collection was recorded. The degree of comfort and satisfaction in objects of sample collection were measured. Results The time spent in sample collection was (22. 84±2. 57)s in the study group, which was shorter than that in the control group (P＜0. 05). The degree of comfort and satisfaction in objects of sample collection were higher than in the study group than those in the control group (P＜0. 05). Conclusion The new type of pharyngeal swab samples collection device is effective to improve the efficiency of sampling in nucleic acid testing. (目的 探讨一种新型咽拭子采集装置在核酸检测中的应用效果。方法 选取核酸采集点进行采样的医务人员120人, 随机分为试验组和对照组, 各60人。对照组采用常规咽拭子采集方法, 试验组采用新型咽拭子采集装置采集。记录两组咽拭子采集时间, 评价被采集对象的舒适度和满意度。结果 试验组咽拭子采集时间(22. 84±2. 57)s, 短于对照组(27. 56±2. 44)s, 差异有统计学意义(P＜0. 05)。试验组舒适度和满意度均高于对照组, 差异有统计学意义(P＜0. 05)。结论 新型咽拭子采集装置能有效提高采样效率。)